Patients with relapsing polychondritis and previous cartilage trauma present more autoimmunity phenomena (2012)
Relapsing polychondritis (RP) is an autoimmune disease characterized by inflammation and destruction of all type of body cartilage, and the cartilage trauma may be a trigger of the disease in a susceptible person. We describe the clinical and laboratory findings in a group of 18 patients with RP with (7 cases) or without (11 cases) anteceding cartilage trauma. The mean age was 41 years in the group with cartilage trauma and 55 years in the group without cartilage trauma. For both groups, female gender was predominant. All patients presented with auricular chondritis. Systemic manifestations and autoimmunity were more common in patients with anteceding trauma. © 2011 Springer-Verlag.